Answer:
x^2 + 4y^2 + 6x + 4
Step-by-step explanation:
Arranging the terms;
x ^ 2 + y^2 + 3y^2 + 4x + 2x + 2 + 2
x^2 + 4y^2 + 4x + 2x + 2 + 2
x^2 + 4y^2 + 6x + 2 + 2
x^2 + 4y^2 + 6x + 4
Answer:
sorry the diagram is not clear......
Answer:
Step-by-step explanation:
Here X no of defective batteries is binomial with p = 1% = 0.01
q = 1-p=0.99
(Because each battery is independent and there are only two outcomes)
Prob that shipment is accepted is for n =36, ![P(X\leq 2)](https://tex.z-dn.net/?f=P%28X%5Cleq%202%29)
=P(x=0,1,2)
= ![\Sigma^2_0 36Cr (0.01)^r (0.99)^{36-r}](https://tex.z-dn.net/?f=%5CSigma%5E2_0%20%2036Cr%20%280.01%29%5Er%20%280.99%29%5E%7B36-r%7D)
= 0.9944
Answer:
- <u>The multiplicative rate of change of the function is 0.5</u>
Explanation:
The <em>multiplicative rate of change</em> is the ratio between consecutive entries.
Naming r the multiplicative rate of change, if it is constant you get:
- r = second entry / first entry = third entry / second entry = fourth entry / third entry.
Here:
- second entry / first entry = 0.125 / 0.25 = 0.5
- third entry / second entry = 0.0625 / 0.125 = 0.5
- fourth entry / third entry = 0.03125 / 0.0625 = 0.5
Thus, the multiplicative rate of change is 0.5. It means that you can obtain each entry as the product of the previous entry times 0.5:
- 0.25 × 0.5 = 0.125
- 0.125 × 0.5 = 0.0625
- 0.0625 × 0.5 = 0.03125
In general, exponential functions have constant multiplicative rate of changes.
Answer:
The answer is 120
Step-by-step explanation: